PENGARUH FLIPBOOK TERHADAP PEMAHAMAN KONSEP BANGUN RUANG KELAS V SEKOLAH DASAR - Agrifina, Vivia Febbrilian; Hermawan, Jody Setya; Rapani; Astuti, Nelly (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effect of using flipbook-based learning media on the understanding of spatial concepts in mathematics subjects for fifth grade elementary school students. The method in this study is a quasi-experimental non-equivalent control group design. The population was 76 students, the sample selection used purposive sampling and the sample used was 52 students. Data collection techniques used tests and non-tests. The results of hypothesis testing with a simple linear regression test, obtained a tcount value> ttable, namely 8.969> 2.056 which indicates an influence and an R square value of 0.744 was obtained which means that 74.4% of the variables in understanding the concept of mathematical spatial geometry material are influenced by the use of flipbook media, while the remaining 25.6% are influenced by other factors outside the variables studied. In addition, the Fcount result of 75.617 with a Sig. value of 0.001 indicates that the regression model used in this study is significant. Furthermore, based on the results of the independent sample t-Test between the experimental class using flipbook media and the control class, it was obtained that tcount> ttable, namely 2.049> 2.009. The results of this hypothesis test prove that there is a significant influence of the use of flipbook media on the understanding of the concept of spatial shapes in the fifth grade mathematics subject at SD Negeri 2 Way Halim Permai.